Assessment of Lipid and Hematological Profile among Blood Donors in European Gaza Hospital, Palestine - Tabash, Ahmad M.; Afana, Wesam M.; Elregeb, Abdrabbou M.; Eid, Sameer Abu; AbuMustafa, Ayman M. (Cardiology and Cardiovascular Medicine, 2019)
Background: There is an important shortage of blood in the greatest blood banks worldwide to meet up with requirements for numerous medical interventions. Limited studies have associated regular blood donation to the lowering of lipid function parameters. Assessing the lipid function is a classical method of evaluating an individual’s risk for coronary heart disease. Objective: The general goal of the study is to determine lipid and hematological profile among blood donors in European Gaza Hospital, Palestine. Materials and Methods: This study was a case-control study that involved 120 males, 40 of whom were regular blood donors (study group), 40 first time donors and 40 non- donors (control group) aged between 18–60 years. A volume of 5ml venous blood was drawn from each fasting participant into a dry biochemistry screw-capped tube. This was allowed to clot and the serum was used to determine total cholesterol (TC), triglycerides, High-density lipoprotein cholesterol (HDL-C), Low-density lipoprotein cholesterol (HDL-C), while HDL-C/LDL-C and TC/LDL ratio were calculated by using the following formula. Anthropometric parameters (weight, height) of donors were measured using standard protocol. The height (in meter), weight (in kilogram) were used to calculate the body mass index (BMI) using the following formula. BMI= weight (kg)/ (height in meter)² and blood was collected from each participant in EDTA (for hematocrit, ESR). Three groups were matched for age and BMI. Data were analyzed using SPSS version 23. Chi-square (χ²) was used to compare the relationship between categorical variables, ANOVA was used to measure the difference between means. Data were summarized using tables, pie charts, histograms. A P-value < 0.05 was considered to be statistically significant for all tests cond